The Effect of Kefir Incorporation on the Physicochemical and Sensory Properties of Bread - Afiza Tan Sali; Tengku Norhidayati Tengku Zainal Abidin; Shahiza Musa (Emerging Advances in Integrated Technology, 2025)
Kefir, a fermented milk beverage from the Caucasus region, is rich in probiotic microorganisms and bioactive compounds. This study aimed to evaluate the effects of kefir incorporation on sensory properties, physicochemical and microbiological bread. Commercial bread is often produced using synthetic additives such as enzymes, preservatives and chemical leavening agents to improve texture, shelf life and volume. There is growing consumer demand for more natural and functional food products. Kefir, a fermented milk beverage rich in probiotics as a natural alternative that may enhance bread quality without the need for synthetic additives. Its application in bread production is still limited and not widely explored. This study focuses on evaluating the suitability of kefir in bread formulations and its effects on the physical, chemical, microbiological, and sensory qualities of bread. This study used three bread formulations, formulation 1 (2.8% yeast and no kefir), formulation 2 (34% kefir and 1.2% yeast) and formulation 3 (48.5% kefir with no yeast). The sensory evaluation using hedonics and scoring indicated that Formulation 2 received the highest scores for aroma, taste, texture and overall acceptability. Physicochemical analysis revealed that this formulation produced bread with desirable textural attributes, including a mean hardness of 5.91 N and elasticity of 5.39 mm. Additionally, it exhibited the highest bread volume (1690 cm³) and specific volume (3.7 cm³/g), indicating enhanced leavening and crumb structure. The pH value of pH 4, attributed to kefir’s natural acidity, contributed to improved microbial stability, with microbial counts as low as Log 2.74 CFU/mL on day 7 of storage suggesting an extended shelf life. In conclusion, the incorporation of kefir at 34% in bread formulation significantly enhances textural quality, microbial safety and sensory acceptance. Kefir presents a viable alternative to conventional fermentation agents in breadmaking. This study was awarded a Gold Medal at the Research; Innovation & Product Launching held in Politeknik Sultan Haji Ahmad Shah Kuantan in 2023. This recognition highlights the innovative potential of kefir-based bread as a functional food product with high quality and commercial viability.